Parade on State Street, ca. 1960 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view east-northeast of a parade on State Street. Buildings line both the north-northwest and south-southeast sides of State Street. Pedestrians line the sidewalks along the street. 2 7/8 x 3 3/4, 3 3/8 x 4 1/4 overall Diffusion transfer prints